EQUIVALENCE OF SOMATIC PHRASEOLOGIES WITH COMPONENT MANUAL LANGUAGE IN GERMAN AND UZBEK (Scientific journal of the Fergana State University, 2023)
The equivalence of the somatic phraseological units with the component “Hand - қўл” in German and Uzbek languages are analyzed in the present article. The full, partial and zero types of equivalents of the somatic phraseological units are enlightened by examples.